PENGARUH CAPITAL ADEQUECY RATIO DAN SOLVABILITAS TERHADAP PERTUMBUHAN LABA DENGAN SUKU BUNGA SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI PERIODE 2019-2022 - Mujiono, Bagas Azrul; Pramitasari, Triska Dewi; Subaida, Ida (Fakultas Ekonomi dan Bisnis, 2024)
This study aims to determine the effect of Capital Adequacy Ratio and Solvency on Profit Growth with Interest Rates as a Moderating Variable in Banking Companies Listed on the IDX for the 2019-2022 Period. The data in this study are secondary data obtained from financial reports. The data collection method in this study is descriptive and quantitative. The population in this study is banking companies listed on the Stock Exchange for 4 years from 2019-2022. The sample used in this study was 9 companies using the Purposive sampling technique. Based on the hypothesis test using the Smart PLS 3.0 application that has been carried out, the results show that the Capital Adequacy Ratio has a positive and significant effect on profit growth, and Solvency has a positive but not significant effect on profit growth. The interest rate moderating variable in this study shows that interest rates significantly moderate the Capital Adequacy Ratio on profit growth and interest rates do not significantly moderate solvency on profit growth.